EPISTEMOLOGI TASAWUF MODERN HAMKA - Muhammad Ainun Najib (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2018)
Abstract Among the modernist Islam is viewed not appreciative to sufism. However, this view does not find truth in Hamka. Through modern sufism, Hamka shows a positive attitude towards sufism. However, in the modern sufism Hamka contains a purification of Sufism. This article shows that the modern sufism Hamka supplemented on the basis of tauhid, unity of the God, and based on Koran and hadith. In contrast to the more classical sufism emphasizes irfani, the modern sufism Hamka using bayani intertwined on the question of the cleansing of the soul and cultivate noble character. He was outlining the subject of war against lust, asketisme, qana'ah, ikhlas, and tawakkal. The purpose of the so that the spiritual emptiness of human beings could be overcome and people became creatures joyness. Keywords: Modern Sufism, Tawhid, Qur’an and Hadith